Influence of the electrodeposition potential on the crystallographic structure and effective magnetic easy axis of cobalt nanowires - Irshad, M.I. (Royal Society of Chemistry, 2016)
Cobalt nanowires (NWs) have been synthesized by electrodeposition inside the pores of anodized aluminium oxide templates, at different values of applied deposition potential. The as-deposited NWs are parallel to one another and exhibit a high geometrical aspect ratio. The crystal structure of these NWs shows a strong dependence on the applied deposition potential during synthesis. X-ray diffraction indicates the predominance of hexagonal-closed-packed (HCP) phase with (002) texture at low applied deposition potentials, whereas a reorientation of the c-axis of the HCP structure is observed for high electrodeposition potentials. Moreover, for a given electrodeposition time, the length of the NWs also increases with the applied potential. As a result of these structural changes, a switch in the magnetic easy axis, from parallel to perpendicular to the NW axis, occurs depending on the applied potential. A simplified model is used to account for this reorientation of the effective magnetic anisotropy direction, which takes into account the interplay between shape anisotropy, magnetocrystalline anisotropy and interwire dipolar interactions. Â© 2016 The Royal Society of Chemistry.